The Canada-U.S. Productivity Puzzle: Regional Evidence of the Pulp and Paper Industry, 1971-2005 - Bernard, Jean-Thomas; Hussain, Md. Jakir (Université d'Ottawa | University of Ottawa, 2015)
We analyze the total factor productivity (TFP) of the pulp and paper industry in three Canadian provinces (British Columbia, Ontario, and Quebec) and in three U.S. states that are contiguously located south of the border (Washington, Illinois, and Maine) over the period of 1971 to 2005. We find that the industry in the three Canadian provinces had much higher TFP growth rates in the era following the Free Trade Agreement (FTA), signed in 1988. In terms of productivity trend, this relative TFP surge has allowed the industry in the three Canadian provinces to move ahead of Illinois and Washington and closer to Maine which is the U.S. leader in the sample. Our results in this particular case do not support the commonly accepted view that Canada has a productivity problem relative to the U.S. / Nous analysons la productivité totale des facteurs (PTF) de l’industrie des pâtes et papiers de trois provinces (Colombie-Britannique, Ontario et Québec) et de celle de trois états américains contigus au sud de la frontière (Washington, Illinois et Maine) au cours de la période allant de 1971 à 2005. Nous trouvons que l’industrie dans les trois provinces canadiennes a connu des taux de croissance de la productivité totale plus élevés après l’Accord de Libre Échange signé en 1988. En ce qui concerne la tendance de la productivité, cette accélération de la PTF a permis à l’industrie de devancer l’Illinois et Washington et de se rapprocher du Maine qui est le meneur aux E.-U. dans notre échantillon. Dans ce cas particulier, notre analyse ne supporte pas le point de vue souvent exprimé que l’industrie canadienne soufre d’un handicap au chapitre de la productivité totale par rapport à leurs compétiteurs américains.
Keywords: Total factor prductivity; income convergence; pulp and paper industry; productivité totale des facteurs; convergence du revenu par habitant; industries des pâtes et papiers